Influence of layer number and sintering temperature on microstructural, tribological, and corrosion behavior of Al2O3-TiO2 multilayer coatings - Eraslan, Fatma Sezgi; Turu, Irem Cemre; Ozcan, Mucahid; Birol, Burak; Gecu, Ridvan (ELSEVIER SCI LTD, 2023)
The effects of layer number (2, 4, and 6-layer) and sintering temperature (800, 900, 1000, and 1100 degrees C) on the microstructure, wear, and corrosion properties of Al2O3-TiO2 multilayer coatings deposited on 316L stainless steel plates using the sol-gel dip coating technique were investigated. The wear characteristics were measured through ball-on-disc type dry sliding tests using an Al2O3 ball under a 1 N load, whereas the corrosion features were determined by potentiodynamic polarization tests conducted in a 3.5 wt% NaCl solution. Anatase, rutile, alpha-Al2O3, and gamma-Al2O3 phases were obtained in the hybrid coatings, depending on the sintering temperatures. However, at 1100 degrees C, the coating did not adhere well to the substrate due to passive oxide film formation on the 316L plate, leading to spalling. Besides, the surface homogeneity deteriorated in the 6-layer coated sample due to higher organic removal and residual stresses. The corrosion rate decreased with the increasing number of layers, but the sensitivity to corrosion varied due to changes in surface properties. The 4-layer coated sample sintered at 1000 degrees C achieved the highest wear strength (improved by up to 71.1%) and corrosion resistance (increased by up to 90.4%) due to its decreased porosity and homogeneously distributed finer particles.
Keywords: Al2O3 -TiO2 hybrid coating; Solgel technique; Multilayer coating; Wear; Corrosion; TIO2 FILMS; ANATASE; RESISTANCE; SUBSTRATE; TRANSFORMATION; STEEL; Materials Science